2023
DOI: 10.36253/jaeid-14510
|View full text |Cite
|
Sign up to set email alerts
|

Economic Analysis of Acid Lime Production and Marketing in Nepal: A Benefit-Cost Perspective from Nawalpur East District

Sudip Ghimire,
Ujjwal Kumar Rauniyar

Abstract: Acid lime plays a crucial role in the livelihoods of many Nepali farmers and holds substantial promise for local economic development. This study analyzed the economic aspects of acid lime production in three municipalities of the Nawalpur East district of Nepal: Madhyabindu, Bulingtar, and Bungdikali, and sought to identify the concerns and potential related to acid lime marketing and manufacturing. Data were gathered from 96 acid lime producers using a semi-structured questionnaire from May 2022 to July 2022… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
0
1
0
Order By: Relevance
“…Preliminary insights into the field conditions, socio-cultural settings, and demographic and topographic features of the study area were acquired through frequent field visits, as suggested by Ghimire and Chhetri (2023), Ghimire and Rauniyar (2023) and Thapa et al (2024). These visits informed the preparation of interview schedules, design of the sampling framework, and application of sampling techniques, facilitating efficient data collection during the subsequent household survey.…”
Section: Survey Design and Data Collection Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Preliminary insights into the field conditions, socio-cultural settings, and demographic and topographic features of the study area were acquired through frequent field visits, as suggested by Ghimire and Chhetri (2023), Ghimire and Rauniyar (2023) and Thapa et al (2024). These visits informed the preparation of interview schedules, design of the sampling framework, and application of sampling techniques, facilitating efficient data collection during the subsequent household survey.…”
Section: Survey Design and Data Collection Methodsmentioning
confidence: 99%
“…Data scores were obtained to assess the level of knowledge of the farmers based on the results of the questionnaire. Indexing was computed using Equation 3 (Dawadi et al, 2023;Ghimire & Kandel, 2023;Ghimire & Rauniyar, 2023;.…”
Section: Problems Rankingmentioning
confidence: 99%
“…Despite these improvements, the production area has witnessed a decline from 1,486,951 ha in 2013/14 to 1,473,474 ha in 2020/21 (MoALD, 2022). Factors such as the introduction of high-yielding varieties and technological advancements have contributed to this growth (Dawadi et al, 2023;Ghimire & Rauniyar, 2023); however, Nepal's rice production remains comparatively low when benchmarked against neighboring countries and the global average. Spring rice varieties, known for their short growth cycle, resilience to pests and diseases, and potential for high yields, are especially promising.…”
Section: Introductionmentioning
confidence: 99%